Learning agility, self-efficacy, and resilience as pathways to mental health in higher education: insights from a mixed-methods study - Huang, He; Kou, Heung (Frontiers in Psychology, 2025)
IntroductionThis study examines how learning agility, academic self-efficacy, academic buoyancy, and psychological well-being interrelate to influence mental health and factors theoretically linked to academic success in undergraduate students.MethodsUsing an explanatory sequential mixed-methods design, quantitative data were gathered from 804 undergraduates using validated scales for each construct. Structural Equation Modeling (SEM) tested hypothesized relationships, and multi-group analysis explored gender differences in the model. In a qualitative phase, semi-structured interviews with 30 participants provided deeper insights into the quantitative findings, with thematic analysis of adaptive learning, resilience, and well-being.ResultsSEM findings showed that learning agility and academic self-efficacy positively predicted academic buoyancy and psychological well-being, with academic buoyancy partially mediating these relationships. Gender differences were non-significant, supporting model generalizability across genders. Qualitative analysis emphasized adaptive learning strategies, resilience in overcoming academic stressors, and psychological well-being as a process, with social support identified as essential in fostering resilience.DiscussionThe findings underscore the importance of learning agility, self-efficacy, and academic buoyancy in supporting students’ academic resilience and mental health. By enhancing these factors within academic settings, institutions can promote student well-being and engagement, reinforcing the link between psychological well-being and academic achievement.